Nanoparticles-Based Face Masks and Respirators for Preventing COVID-19 Transmission: Breathability Versus Biocidal Activities - Saminan Saminan; Linda Julisafrida; Sakdiah Sakdiah; Ratna Idayati; Nurul Fajri; Muhammad Iqhrammullah (Institute of Medico-legal Publications Pvt Ltd, 2021)
Use of face masks and respirators are significant in preventing the transmission of coronavirus disease 2019(COVID-19) via respiratory droplets or aerosols. The development of face masks and respirators have beenfocused on the modification using nanoparticles (NPs) to obtain biocidal activities. The incorporation ofNPs can also increase the hydrophobicity of the material that assists the repelling of virus carrying dropletsor aerosols. Nevertheless, the common cost of gaining those benefits is breathability. Previous studies havereported on the discomforts of wearing a face mask or respirator, one of which is stems from breathingdifficulty. At the time of pandemic, maintaining the comfort wearing of face masks or respirators is evenmore crucial. Thus, this review article is important to keep the breathability aspect gaining a spotlight inthe development of NPs-modified face masks or respirators. Herein, we discuss the relationship betweenthe addition of NPs with breathability of the material. In the beginning of discussion, types of protectiverespiratory equipments, and biocidal activities of the modified fabrics are discussed. Strategies in maintainingthe air permeability for long duration use and self-cleansing feature are also discussed.